2013
DOI: 10.1021/ma400208j
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time and in Situ Investigation of “Living”/Controlled Photopolymerization in the Presence of a Trithiocarbonate

Abstract: Polymerization of methyl acrylate under ultraviolet (UV) irradiation in the presence of S-1-dodecyl-S′-(α,α′-dimethyl-α″-acetic acid) trithiocarbonate (DDMAT) was investigated by in situ 1H nuclear magnetic resonance spectroscopy. Effects of light intensity, wavelength, and concentration of DDMAT on the polymerization behaviors were studied in detail. The experimental results demonstrate that the “living” features of the photopolymerization are related to the concentration of DDMAT. “Living”/controlled radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 32 publications
9
129
0
Order By: Relevance
“…Similar to the pre-test results in Table 1, blue light gave the highest polymerization rate (k p app = 9.3 × 10 -3 min -1 , based on assumption and estimation of linear kinetic plotting) and shortest induction period (60 min), while green light gave k p app equal to 3.5 × 10 -3 min -1 with 220 min induction period, whereas k p app for red light was close to zero. The induction period observed in the polymerization can be attributed to stable and long lifetime intermediate of radical addition product in the RAFT process, which was observed in conventional RAFT polymerization and proved by other research groups (33,87).…”
Section: Mma Polymerization Mediated By Cdtpa Under Blue and Green LIsupporting
confidence: 53%
“…Similar to the pre-test results in Table 1, blue light gave the highest polymerization rate (k p app = 9.3 × 10 -3 min -1 , based on assumption and estimation of linear kinetic plotting) and shortest induction period (60 min), while green light gave k p app equal to 3.5 × 10 -3 min -1 with 220 min induction period, whereas k p app for red light was close to zero. The induction period observed in the polymerization can be attributed to stable and long lifetime intermediate of radical addition product in the RAFT process, which was observed in conventional RAFT polymerization and proved by other research groups (33,87).…”
Section: Mma Polymerization Mediated By Cdtpa Under Blue and Green LIsupporting
confidence: 53%
“…In contrast, the nanogel (overall modified I2959 concentration of 44.2 mM) showed almost no induction time (Figure 2). This is due to the potential for RAFT agents to cleave into radicals and initiate polymerization under UV light 32, 33 . It was confirmed that a variety of RAFT agents, including dithioester (Figure S4) and trithiocarbonate (data not shown) were able to initiate monomer polymerization under the same irradiation conditions even in the absence of photoinitiator.…”
Section: Resultsmentioning
confidence: 99%
“…carbon-centred radical) state, therefore dramati-cally lowering the instantaneous radical concentration in solution as a means to preclude termination reactions. 48 Building on earlier reports of direct photoactivation of thiocarbonylthio-containing RAFT agents under UV irradiation, [49][50][51][52][53][54] we recently reported the direct photoactivation of these compounds (specifically trithiocarbonates (TTCs)) using visible light for the synthesis of well-defined poly(acrylates) and poly (acrylamides). These two approaches are illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%